Superior humoral immunity in vaccinated SARS-CoV-2 convalescence as compared to SARS-COV-2 infection or vaccination - Paniskaki, Krystallenia; Konik, Margarethe J.; Anft, Moritz; Meister, Toni L.; Marheinecke, Corinna; Pfaender, Stephanie; Jäger, Jasmin; Krawczyk, Adalbert; Zettler, Markus; Dolff, Sebastian; Westhoff, Timm H.; Rohn, Hana; et al. (Frontiers in Immunology, 2022)
Emerging variants of concern (VOC) raise obstacles in shaping vaccination strategies and ending the pandemic. Vaccinated SARS-CoV-2 convalescence shapes the current immune dynamics. We analyzed the SARS-CoV-2 VOC-specific cellular and humoral response of 57 adults: 42 convalescent mRNA vaccinated patients (C+V+), 8 uninfected mRNA vaccinated (C-V+) and 7 unvaccinated convalescent individuals (C+V-). While C+V+ demonstrated a superior humoral SARS-CoV-2 response against all analyzed VOC (alpha, delta, omicron) compared to C-V+ and C+V-, SARS-CoV-2 reactive CD4+ and CD8+ T cells, which can cross-recognize the alpha, delta and omicron VOC after infection and/or vaccination were observed in all there groups without significant differences between the groups. We observed a preserved cross-reactive C+V+ and C-V+ T cell memory. An inferior humoral response but preserved cross-reactive T cell memory in C+V- compared to C+V+ was observed, as well as an inferior humoral response but preserved cross-reactive T cell memory in C+V- compared to C-V+. Adaptive immunity generated after SARS-CoV-2 infection and vaccination leads to superior humoral immune response against VOC compared to isolated infection or vaccination. Despite the apparent loss of neutralization potential caused by viral evolution, a preserved SARS-CoV-2 reactive T cell response with a robust potential for cross-recognition of the alpha, delta and omicron VOC was detected in all studied cohorts. Our results may have implications on current vaccination strategies.